2020
DOI: 10.1111/1462-2920.14925
|View full text |Cite
|
Sign up to set email alerts
|

7‐hydroxytropolone is the main metabolite responsible for the fungal antagonism of Pseudomonas donghuensis strain SVBP6

Abstract: Summary Pseudomonas donghuensis strain SVBP6, an isolate from an agricultural plot in Argentina, displays a broad‐spectrum and diffusible antifungal activity, which requires a functional gacS gene but could not be ascribed yet to known secondary metabolites typical of Pseudomonas biocontrol species. Here, we report that Tn5 mutagenesis allowed the identification of a gene cluster involved in both the fungal antagonism and the production of a soluble tropolonoid compound. The ethyl acetate extract from culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 58 publications
6
41
0
1
Order By: Relevance
“…In addition, our P. donghuensis 22G5 showed a higher amount of 7-HT production (the OD 330 of 7-HT produced by 22G5 reached 4 to 5 when the OD 600 of the culture reached 2) (Fig. 4 d) compared with that reported for P. donghuensis SVBP6 (Muzio et al 2020 ) (the OD 330 of 7-HT produced by SVBP6 reached 1 when the OD 600 of the culture reached 2). Moreover, our data from the in planta assay first showed the effectiveness of P. donghuensis against V. dahliae , and this further supported its applications in the development of BCAs for VW manipulation in cotton farming.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…In addition, our P. donghuensis 22G5 showed a higher amount of 7-HT production (the OD 330 of 7-HT produced by 22G5 reached 4 to 5 when the OD 600 of the culture reached 2) (Fig. 4 d) compared with that reported for P. donghuensis SVBP6 (Muzio et al 2020 ) (the OD 330 of 7-HT produced by SVBP6 reached 1 when the OD 600 of the culture reached 2). Moreover, our data from the in planta assay first showed the effectiveness of P. donghuensis against V. dahliae , and this further supported its applications in the development of BCAs for VW manipulation in cotton farming.…”
Section: Discussionsupporting
confidence: 49%
“…3 b). We further compared P. protegens XY2F4 and P. donghuensis 22G5 genomes respectively with more published strains in the same species, including two well-documented P. protegens strains (Paulsen et al 2005 ; Shaukat and Siddiqui 2003 ) and three published P. donghuensis strains to date (Chen et al 2018 ; Muzio et al 2020 ; Ossowicki et al 2017 ). Results indicated that the P. protegens XY2F4 genome had 835 specific genes compared with P. protegens CHA0 and Pf-5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NL81, which was in contrast to previous studies reporting adverse effects of pyoluteorin against protists (Winding et al, 2004;Jousset et al, 2006). An additional candidate antibiotic compound, 7-hydroxytropolone, was recently reported for P. donghuensis SVBP6 to be at the origin of the broad-spectrum in vitro antifungal activity displayed by this bacterium (Muzio et al, 2020). Tropolone and products containing tropolonoid motifs display antimicrobial activities attributed to their metal-chelating and redox properties (Guo et al, 2019) and derivatives have shown some anti-protozoan activities (Ren et al, 2003).…”
Section: Bacterial Traits Correlated To Predation Resistancementioning
confidence: 78%